ANALISIS RESIKO, MANFAAT DAN KEMUDAHAN PENGGUNA SERTA DAMPAKNYA PADA KEPERCAYAAN NASABAH DALAM MENGGUNAKAN SMS BANKING PT. BANK ACEH SYARIAH BANDA ACEH - Marlizar Marlizar; Fitriyanti Irmas; Nurmala Nurmala; Lisnawati Lisnawati (Program Pascasarjana IAIN Langsa, 2020)
This study aims to analyze the effect of risk, benefit and userconvenience on customer trust in using SMS Banking at PT. BankAceh Syariah Banda Aceh. The sample of this study was 96respondents and the sample was taken using purposive samplingtechnique. The research data were collected through questionnairesand documentation study. The data analysis technique usedmultiple linear regression analysis. The results showed thatsimultaneously the variables of risk, benefit and convenience ofusers had an effect on customer trust in using SMS Banking at PT.Bank Aceh Syariah Banda Aceh. Then partially the variables ofbenefits and user convenience affect customer confidence in usingSMS Banking at PT. Bank Aceh Syariah Banda Aceh. While the riskvariable has no effect on customer confidence in using SMSBanking at PT. Bank Aceh Syariah Banda Aceh.